Venture deals : be smarter than your lawyer and venture capitalist - Feld, Brad; Mendelson, Jason, 1971- (John Wiley & Sons, Inc., 2016)
"In this updated Venture Deals, Third Edition, they will use their years of experience in venture capital and early stage investing to show entrepreneurs how to succeed and prosper, outlining the essential elements of the venture capital term sheet and the tactics needed to negotiate."--